2009
DOI: 10.1080/03630240903238776
|View full text |Cite
|
Sign up to set email alerts
|

Risk Messages About HPV, Cervical Cancer, and the HPV Vaccine Gardasil: A Content Analysis of Canadian and U.S. National Newspaper Articles

Abstract: The human papillomavirus vaccine (Gardasil) is a significant advancement in women's health. We compared the reporting of fearinducing messages about human papillomavirus, cervical cancer, and the human papillomavirus vaccine in Canadian and U.S. national newspapers between January 2006 and December 2007. Significant differences between countries were found in the number of articles containing fear messages about human papillomavirus, cervical cancer, and the human papillomavirus vaccine. Educational level of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…Greece seems to lag behind, as compared to US figures of 37% at similar time lag after inclusion [32]. Recent inclusion, negative publicity, and doubts on the vaccine's efficacy and safety may have contributed to the particularly low uptake [1,16]. To increase HPV coverage, interventions may be informed by the Central European Vaccination Advisory Group guidelines, suggesting administration at the same visit with other vaccines and school-based immunizations [27].…”
Section: Discussionmentioning
confidence: 98%
“…Greece seems to lag behind, as compared to US figures of 37% at similar time lag after inclusion [32]. Recent inclusion, negative publicity, and doubts on the vaccine's efficacy and safety may have contributed to the particularly low uptake [1,16]. To increase HPV coverage, interventions may be informed by the Central European Vaccination Advisory Group guidelines, suggesting administration at the same visit with other vaccines and school-based immunizations [27].…”
Section: Discussionmentioning
confidence: 98%
“…4 Researchers also found that the vaccine was increasingly described as controversial over the course of the debate. This was particularly so after states began to consider requiring the vaccine for school-age girls.…”
Section: Background On the Issuementioning
confidence: 99%
“…As to visibility of 'fright factors' investigated in other media analyses (Abdelmutti & Hoffman-Goetz, 2009;Bennett, Calman, & Curtis, 2009;Burke, 2012;Deignan et al, 2013;Ekberg, 2007;Granatt, 2004;Meara, 2002;Verbeke, Frewer, Scholderer, & De Brabander, 2007), they were very little present in the newspapers we covered; for the most part we observed that articles especially from the Edmonton Journal and the Calgary Herald have a very upbeat tone regarding greening and are about businesses and individuals who are 'greening' their actions. However, it is not quite clear how much of an impact this upbeat coverage has especially as the economic factor was so evident.…”
Section: Discussionmentioning
confidence: 92%